Integrated MARTE-based model for designing component-based embedded real-time software - Mohd. Zaki, Mohd. Zulkifli (Science and Engineering Research Support Society, 2015)
Recently, modeling and implementation of Embedded Real Time System (ERTS) are unavoidably becoming more complicated to develop and be reused because of the increasingly complex design. The complexity is due to the functionality increment factor in accordance with users' needs and demands, resulting in the growing scale of the developed systems. The current development approach based on Object-Oriented (OO) does not match the current requirements of the system. The OO approach has numerous flaws, thus, Component-Based Software Engineering (CBSE) has been appointed to resolve those problems. However, the current CBSE approach also has some drawbacks such as lack of ERTS standardized modeling and specific development methodology. The problems concerning the established ERTS development methodologies, Methods for Component-Based Real-Time Object-Oriented Development Testing (MARMOT) shows the capabilities to tackle ERTS modeling and implementation using CBSE strategy are partially provide the required standard modeling language for development tool adaptation. Thus, an integrated component model is proposed, by integrating MARMOT and a Unified Modeling Language (UML) profile known as Modeling and Analysis for Real-Time and Embedded (MARTE), which can be adapted to the CBSE approach standard modeling. In addition, the proposed model can improve the existing MARMOT software process. The findings showed that the proposed model has reduced ERTS development complexity by enhancing the design mechanisms.